Inovasi Penilaian Otentik dalam Pembelajaran Bahasa Arab Maharah Kitabah Pada Buku Bahasa Arab Kelas VII Madrasah Tsanawiyah Terbitan Kemenag 2020 - Maspeke, Nurul Muthaharaini; Baroroh, R. Umi; Mandaka, Dwi Arian Putra; Wahyuni, Heni; Nur, Yusril Muhammad (STIQ Amuntai, 2024)
This research aims to analyze and answer the problems that exist in the assessment of class VII Arabic books published by the Ministry of Religion of the Republic of Indonesia in 2020, especially regarding writing skills. This research uses descriptive qualitative methods and literature studies to collect data. This scientific research only offers innovation to carry out authentic assessments as a solution to problems that occur in assessments in Arabic books published by the Ministry of Religion in 2020